Study the role of intercellular mediators in the metabolism of connected tissue in children with cardiomyopathy and osteopeny = Вивчення ролі міжклітинних медіаторів у метаболізмі сполучної тканини у дітей з кардіопатією та остеопенією - S. B. Pavlov; G. B. Pavlova (Kazimierz Wielki University, 2016)
Pavlov S. B., Pavlova G. B. Study the role of intercellular mediators in the metabolism of connected tissue in children with cardiomyopathy and osteopeny = Вивчення ролі міжклітинних медіаторів у метаболізмі сполучної тканини у дітей з кардіопатією та остеопенією Journal of Education, Health and Sport. 2016;6(9):902-916. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163528 http://ojs.ukw.edu.pl/index.php/johs/article/view/3961       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016.   study the role of intercellular mediators in the metabolism of connected tissue in children with cardiomyopathy and osteopeny   Kharkiv Medical Academy of Postgraduate Education   S. B. Pavlov, G. B. Pavlova   Abstract Introduction. Undifferentiated forms of connective tissue dysplasy (UCTD) characterized by multiple organ changes and represent significant difficulties in diagnosis, prognosis assessment and correction capabilities. The most significant changes are manifestations UCTD musculoskeletal and cardiovascular system. However, to date, unclear mechanisms of cytokine regulation of metabolism CT, providing optimum intercellular interaction. Objective - determine the profiles intercellular mediators and their significance in the development of common disorders scheme remediation regulation of connective tissue (CT) in children with cardiomyopathy and osteopeny. Materials and Methods Investigated group consisted of 80 children with cardiomyopathy and osteopeny aged 8 to 14, boys - 42 Girls - 38 control group consisted of 30 healthy children of similar age. We investigated the content of RANKL, OPG, IL-1 RA, IL-17, TGF-1β, visfatyn and adiponectin in serum by enzyme immunoassay. Results of the study established that the development of osteopeny associated with an imbalance in the system: ligand receptor activator of nuclear factor κβ (RANKL) / receptor activator of nuclear factor κβ (RANK) / osteoprotegerin (OPG), which leads to activation osteoklastoheneza and increased bone resorption. The content of RANKL and OPG children in the study group was significantly higher than in the control group (RANKL - 0.28 ± 0.02 pmol / l at a rate of 0.21 ± 0.02 pmol / L (p <0,05); OPG 74.7 ± 3.62 pg / ml at a rate 62.9 ± 2.48 (p <0.05)). There was a violation adypokinovoho exchange and reduced production of the cytokine IL-17, which is a direct inducer fibroblasts. Average levels of IL-1 RA, IL-17 adiponectin and visfatyne significantly decreased and were: IL-1 RA - 169 ± 14.2 pg / ml at a rate of 264 ± 12.3 pg / ml (p <0.05), IL-17 - 13.9 ± 0.43 pg / ml at a rate of 30.2 ± 1.26 (p <0.05) Adiponectin - 18.3 ± 0.23 mg / ml at a rate of 20.9 ± 0.22 mg / ml (p <0.05) visfatyn -158 ± 7.4 ng / ml at a rate of 158 ± 7.4 ng / ml (p <0.05). Changes in the expression of TGF-1β was detected. Conclusions. In children with cardiomyopathy and osteopeny in the background UCTD there is an imbalance in the system of regulation of the functional system of connective tissue (FSCT) at intercellular mediators who manifested the presence of pathological processes of biosynthesis deactivation CT. Identified changes may indicate a violation of a framework for the regulation of CTs remodeling and reduction of reserves of adaptation that should see the continued dynamic processes of remodeling and disease Keywords: cardiovascular diseases, diseases of the musculoskeletal system, connective tissue dysplasia, intercellular mediators, childhood diseases   Вивчення ролі міжклітинних медіаторів у метаболізмі сполучної тканини у дітей з кардіопатією та остеопенією   Харківська медична академія післядипломної освіти   С. Б. Павлов, Г. Б. Павлова   Резюме Вступ. Недиференційовані форми дисплазії сполучної тканини (НДСТ) характеризуються поліорганними змінами і представляють значні труднощі в діагностиці, оцінці прогнозу і можливості корекції. Найбільш значущими проявами НДСТ є зміни опорно-рухового апарату та серцево-судинної системи. Однак до теперішнього часу, не з'ясовані механізми цитокінової регуляції метаболізму СТ, які забезпечують оптимальну міжклітинну взаємодію. Метою роботи було визначення  профілів міжклітинних медіаторів та їх значущість у розвитку порушень загальної схеми регуляції процесів ремоделяції сполучної тканини (СТ) у дітей з кардіопатією та остеопенією. Матеріали і методи Досліджувану групу склали 80 дітей з кардіопатією та остеопенією віком від 8 до 14 років, хлопчиків - 42, дівчаток - 38.  Контрольну групу склали 30 здорових дітей аналогічного віку. Досліджували вміст RANKL, OPG, IЛ-1 RA, ІЛ-17,  TGF-1β, адипонектину та вісфатину у сироватці крові методом імуноферментного аналізу. Результати дослідження Встановлено, що розвиток остеопенії пов'язаний з дисбалансом у системі: ліганд рецепторного активатора нуклеарного фактора κβ (RANKL)/рецепторний активатор нуклеарного фактора κβ (RANK)/остеопротегерин (OPG), що призводить до активації остеокластогенеза і підвищення кісткової резорбції. Вміст RANKL та OPG у дітей досліджуваної групи був достовірно вищим, ніж в контрольній групі (RANKL - 0.28±0.02 пмоль/л при нормі 0.21±0.02 пмоль/л (р<0,05) ; OPG 74.7±3.62 пг/мл при нормі 62.9±2.48 (р<0,05)). Спостерігалося порушення адипокінового обміну і зниження продукції цитокіну ІЛ-17, що є прямим індуктором фібробластів.